Exploitation of Biocontrol Agents as an Alternative Strategy to Control Post Harvest Diseases of Fruits - Kumari, Neelam; Singh, Deepika; Thakur, Ashok K. (International Journal of Economic Plants, 2016)
There is an increasing concern about the environmental effects and safety of chemical pesticides and fungicides all over the world. Microbial biocontrol agents possess a number of important advantages over traditional chemical pesticides which make their commercial outlook particularly promising and can be commercially developed with relative ease to control post harvest diseases of fruits. Biological control of different plant diseases was focused primarily using bacteria or filamentous fungi and so, application of yeastsas biocontrol agents acts as a new trend against different pathogens. Various observations suggest thatcompetition for space and nutrients between biocontrol agents and pathogens, antibiosis, parasitism, induction of hostresistance and also resistance to oxidative stress are likely to be the main mechanisms of action. Products based on biocontrol agents have a share of 30% in total biopesticide market. There is still a need for research to develop suitable formulations of biopesticides from these microbial biocontrol agents. This review reveals that extensive ecological research is also required in order to achieve optimum utilisation of biological resources to manage various postharvest diseases of fruits.